Sosiologi Hukuman Edukatif di Pondok Pesantren Nurrus Sa’adah Banyumas: Studi tentang Ta’zir, Disiplin Moral, dan Legitimasi Pengasuhan Santri - Tiyas Endah Sulistiyanah; Muh. Hanif (Al-Khazin: Jurnal Pendidikan Agama Islam, 2026)
Islamic boarding schools (pesantren) utilize ta'zir as an educational punishment instrument to develop the moral discipline of students (santri). This practice is grounded in the strong legitimacy of traditional caregiving within pesantren, yet its implementation often faces challenges regarding the boundary between disciplinary enforcement and perceptions of violence. This study aims to explain the empirical practices of implementing ta'zir, the dynamics of social relations formed within it, and its implications for religious education in pesantren. This research employs a pesantren caregiving study approach. Data were collected through direct observation, in-depth interviews with administrators and students, and documentation analysis related to the internal regulations of the boarding school. The results of the field data analysis indicate that ta'zir is imposed for various concrete violations, such as tardiness, absence from mandatory activities, violations of etiquette, and possession of prohibited items. In practice, administrators communicate these punishments using the language of guidance, emphasizing responsibility and self-improvement. Meanwhile, students’ perceptions of ta'zir vary. Some students accept and internalize it as part of the educational process, while others feel psychologically and physically burdened by it. Theoretically, this article contributes to the sociology of Islamic education by demonstrating that ta'zir in pesantren functions as an effective mechanism of moral discipline legitimized by caregiving traditions. Its effectiveness depends on the consistent understanding and implementation of ta'zir as an educational instrument rather than an act of violence.